Les inscriptions romanesques dans la prose arthurienne du XIIIe au XVe siècle - Hériché Pradeau, Sandrine (Éditions universitaires de Dijon, 2024)
Arthurian novelistic prose (thirteenth to fifteenth centuries) uses narrative to deliberately refer to written traces to be read by a fictitious reader, most often a wandering knight in search of meaning. Based on a large corpus—Lancelot-Grail, the sequel to the Prose Merlin, Prophecies of Merlin, Prose Tristan, Prose Meliadus and Guiron le Courtois, Perceforest, and Livre du Cuer d’Amor espris de René d’Anjou (allegorical novel by the duke René d’Anjou)—these traces are considered from literary, poetic, linguistic, and historical standpoints. How are written traces used to investigate the notions of authority, space, orality, and memory? Given that they consist of writing, and thus image, to what extent can they be perceived as a mental or material imago? Once they manifest the dual sacramental/saint and magic/diabolic aspect of writing, written traces also frequently participate in magic and prophetic practices, which prose writers take pleasure in highlighting. In prose but also in verse—anonymous or signed; brief or prolix; shifting, illegible, or monumental; inscribed on metal, stone, wood, or flesh—novelistic traces possess multiple facets that have much to say about writing’s power in the Middle Ages.